Output-Based Aid in Armenia : Connecting Poor Urban Households to Gas Service - Balabanyan, Ani (World Bank, Washington, DC, 2012)
Gas-based heating offers a clean, efficient, low-cost heating solution for poor urban households in Armenia, a country with severe winters. But many low-income households cannot afford the cost of connecting to gas networks and heating facilities or the cost of heating equipment. To help these families benefit from gas-based heating, Global Partnership on Output Based Aid (GPOBA) and the World Bank are funding a scheme that provides grants to eligible poor households for individual heating solutions, based on a gas heater, or local heating solutions, based on a boiler. Disbursement of the funds is tied to the delivery of preagreed outputs, creating incentives for the service providers to ensure timely completion of the installation work and early delivery of gas or heat supply. Up to 10,000 poor urban households (4,600 through the GPOBA funds) are expected to benefit.